ECO ENZYME: PENGOLAHAN SAMPAH RUMAH TANGGA MENJADI PUPUK MULTIFUNGSI DI DESA TULANG BAWANG BARU - Susanti, Agus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Garbage is one of the problems faced by many cities around the world. Indonesia is one of the developing countries that contributes the largest waste in the world. Indonesia is the second largest waste contributor with a volume of 187.2 million tons/year, with China in first place with 262.9 million tons/year. In 2003, a doctor from Thailand named Dr. Rosukon Poompanvong received an award from the FAO for the discovery of eco enzyme. The problem of waste in urban areas is a concern in activities. Around 80% of the total amount of waste produced is dominated by organic waste which is only seen as waste that has no economic value. Therefore, this program is an empowerment for housewives so that they can use organic kitchen waste that is not used to be beneficial for the environment. Community service activities were carried out in the form of socialization and training on the manufacture of eco-enzyme multipurpose liquid. Organic waste can be processed into eco enzyme which is useful as a cleaning fluid, wound medicine, and plant fertilizer. Socialization activities and training on making eco-enzyme multipurpose liquid were carried out at the Tulang Bawang Baru Village Hall, Bunga Mayang District, North Lampung, Lampung Indonesia directly by implementing strict health protocols. Socialization activities and training on making eco enzyme were attended by representatives of residents to prevent crowds. This activity aims to make the Sangkrah Village community able to utilize organic waste so that it can be utilized and even add economic value to the surrounding community. However, the target remains enthusiastic in participating in this activity.